Pengaruh Global Mindset, Karakteristik Pekerjaan Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. SMAB PANDAAN - Khalishah, Salsabila Rohadatul Aisy; Khalikussabir, Khalikussabir; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The aim of this research is to examine the effect of Global Mindset, Job Characteristics, and Compensation on Employee Performance at PT. SMAB Pandaan, both individually and simultaneously, as well as to identify the variable that has the most significant influence. The study employs a quantitative approach with hypothesis testing. A total of 75 employees of PT. SMAB Pandaan were selected as the research sample. Primary data were collected through a Likert-scale questionnaire, followed by validity and reliability testing. Data analysis was conducted using multiple linear regression, the coefficient of determination (R²), t-test, F-test, and classical assumption tests with the assistance of SPSS version 19 for Windows. The findings indicate that Global Mindset, Job Characteristics, and Compensation have both partial and simultaneous effects on Employee Performance. Among the three variables, Global Mindset is the most influential factor. Overall, the three independent variables demonstrate a strong and positive relationship with Employee Performance. Keywords: Global Mindset, Compensation, Job Characteristics, Employee Performance.